Empat Prinsip Komposisi Menciptakan Desain Indah, Satu Trik Pemikat Hati Pemirsa: Rhythm, Depth, Balance, Unity - Emphasis - Julianto Julianto (Bina Nusantara University, 2011)
Rhytm, depth, balance, unity are 4 main visual composition principles which are abbreviated and simple. The design principles made it easier to design beautiful visual communication but still reflecting strong effects for audience in extracting one trick of desain principles: emphasis. The article adapts literature study method from 7 popular books about visual design communication, along with information beneath each book. The analysis consists of descripted important parts in design principles, then summarize them into 4 (rhythm, depth, balance, unity) plus 1 (emphasis). The article hopefully could facilitate lecturers and students in learning process in DKV classes.